PENGEMBANGAN MODEL PELATIHAN SOFT-SKILLS PADA SISWA SEKOLAH MENENGAH PERTAMA NEGERI (SMPN) DI KOTA MATARAM - Darmiany, Anik (Jurnal Kajian Bimbingan dan Konseling, 2016)
Research and development is aimed to produce soft-skills training models especially in communication skills and emotional control student junior high school (SMP) in Mataram city. Research and development method is carried out through three stages from the ten steps of Borg & Gall, they are; (1) the preliminary research (needs analysis), (2) the development of training model, (3) Model evaluation and try out. The results show that the development of soft-skills training model develop training manual for counselors and students, as well as soft-skills training materials that meet acceptable criteria of usability, usefulness and feasibility. Besides, the results showed also that there is a difference in scores between pre-test and post-test in skills at managing emotions from unskilled to be very skilled, and communication skills from unskilled become quite skilled.